Millennials and corporate culture in multinational companies - Viorina Maria Judeu (Agora International Journal of Economical Sciences (AIJES), 2016)
Globalization is not what it was a decade ago. What links the world together has changed fundamentally. For many companies, succeeding in this new operating environment will require rethinking many past decisions and assumptions.Multinational companies hire Millennials because they appreciate their energy and initiative. On the other hand, Millennials greatly values the personal time and are not willing to provide the tray dedication and energy. When organizational structures expect these things to come by itself, may be disappointed. Millennials are carefully selected and their involvement. Millennials have to be earned, not to be taken for granted.
Keywords: 330